Atypical Color Preference in Children with Autism Spectrum Disorder - Grandgeorge, Marine; Masataka, Nobuo (Frontiers in Psychology, 2016)
So far, virtually no study has ever investigated color preference in children with autism spectrum disorder (ASD). In order to address this issue, 29 boys with ASD varying in age between 4 and 17 years, and 38 age-matched typically developing (TD) boys were studied regarding their preference among six colors: red, pink, yellow, brown, green, and blue, in clinical settings. When mean rank of preference was computed in each of the ASD and TD groups with regard to each color, it was found that boys with ASD were significantly less likely than TD boys to prefer yellow and more likely than TD boys to prefer green and brown colors. These results appear to be caused by hyper-sensation characteristic of ASD, due to which boys with this disorder perceive yellow as being sensory-overloading.